The Effects of Turmeric Acid Consumption and Yoga on Young Women's Dysmenorrhea - Gustina, Gustina; Safitri, Safitri (Jurnal EduHealth, 2022)
Dysmenorrhea is menstrual pain that occurs for one to several days during menstruation and is the main gynecological problem that women often complain about dysmenorrhea is stiffness or cramping in the lower part before or during menstruation. Dysmenorrhea has a very bad impact on female students because it causes interference in teaching and learning activities, does not pay attention or does not focus in depth when giving explanations, and some sleeping in class during teaching and learning activities affect academic and non-academic achievements. Many female students complain when they feel menstrual pain, so they don't go to college. Management of menstrual pain (dysmenorrhea) can be done through pharmacological and non-pharmacological measures. Efforts to treat menstrual pain (dysmenorrhea) with stretching exercises and drinking water therapy are effective for non-pharmacological measures in reducing pain or menstrual pain. Another non-pharmacological action using herbal plants is sour turmeric drink. This study determined the influence of the habit of drinking turmeric acid and yoga in overcoming dysmenorrhea. Quasi-experimental research method, one group measuring pain level with a Numeric Rating Scale (NRS) for dysmenorrhea using pretest and posttest questionnaires. The only sample who drank turmeric acid and had not done yoga were 30 young women. The results of young women had a significant effect on the treatment of dysmenorrhea before and before taking turmeric acid and doing yoga with p value < 001.